Immunotherapy with interleukin-2: A study based on mathematical modeling - Banerjee, Sandip (Zielona Góra: Uniwersytet Zielonogórski)
The role of interleukin-2 (IL-2) in tumor dynamics is illustrated through mathematical modeling, using delay differential equations with a discrete time delay (a modified version of the Kirshner-Panetta model). Theoretical analysis gives an expression for the discrete time delay and the length of the time delay to preserve stability. Numerical analysis shows that interleukin-2 alone can cause the tumor cell population to regress.
Keywords: effector cells; tumor cells; interleukin-2; discrete time delay